SIO2 PRECIPITATION IN OLIVINE: ATEM INVESTIGATION OF TWO DUNITES ANNEALED AT 300 MPA IN HYDROUS CONDITIONS - Raterron P.; Chopra P.; Doukhan J.C. (My University, 2000)
Two natural dunites were annealed at pressure P=300 MPa, temperature T=1373, 1473 and 1573 K, and fO2 within the stability field of olivine. The starting materials contained small amounts of hydroxyls in the form of minor phases of hydrated minerals, which released an aqueous phase during the experiments. A detailed analytical transmission electron microscopy (ATEM) investigation of these materials revealed that small quantities of two types of silica-rich glass formed during heat treatment. The first type of glass, found at triple junctions as rare partially crystallized glass pockets, results from melting dehydration reactions involving the hydrous phases. The second type of glass is found as pure silica precipitates (0.1-0.5 μm in size, for a total of a few 0.1 vol%) within the olivine grains of specimens heated to =<1473 K. From considerations of the kinetics of the precipitation at 1473 K, we interpret this silica precipitation as resulting from the condensation of olivine metallic vacancies promoted by increasing fluid fugacities during the runs. Our observations, thus, demonstrate that metastable silica can precipitate in olivine from dunites experiencing rapid changes in their thermodynamical environment.
Keywords: OLIVINE; DUNITE; TRANSMISSION ELECTRON MICROSCOPY; SILICA; PRECIPITATION; EXSOLUTION; POINT DEFECTS; ULTRAMAFIC COMPOSITION; XENOLITHS